A novel path towards limiting non-exhaust particulate matter emissions of a commercial friction material through the addition of metallurgical slag - Jayashree, Priyadarshini; Matějka, Vlastimil; Leonardi, Mara; Straffelini, Giovanni (Scientific reports, 2023)
Keeping recycling and the circular economy in mind, this study explores the reduction in emission of a highly optimized, commercially employed friction material formulation through the addition of metallurgical slags from a basic oxygen furnace in varying quantities from 6 to 38 wt%. The various compositions were paired with a pearlitic grey cast iron counterface and tested on a pin on disc tribometer. The friction coefficient and pin wear increased with the slag addition but were still within the permissible limit when compared to the original formulation. Specimens with higher slag content observed extremely compacted and extended secondary contact plateaus, which also recorded significant slag presence. The extended plateaus detached in the form of chunks from the mating surfaces, which settled on the equipment hardware and restricted the production of airborne particles. From an industrial symbiosis perspective, the addition of metallurgical slags proved to be a promising way of obtaining green friction materials with reduced emissions.